2018
DOI: 10.1093/ibd/izy278
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adipose Tissue Is Associated With Stricturing Crohn’s Disease Behavior, Fecal Calprotectin, and Quality of Life

Abstract: VAT:SAT, rather than BMI, is associated with stricturing CD behavior, elevated FC, and reduced QoL in a disease distribution-dependent manner. Further studies are required to substantiate the role of VAT as a useful biomarker in CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 26 publications
1
30
1
Order By: Relevance
“…Studies in patients with CD disease using visceral adiposity as a measure of obesity have more consistently shown the increased risk of CD-related complications than those using BMI as a marker of overall obesity [58][59][60][61][62][63][64]. Erhayiem et al [58], in a study on 97 patients with CD, found that using computed tomography (CT) scanning that mesenteric fat index (MFI), defined as the ratio of areas of visceral-to-subcutaneous fat was a good marker of aggressive CD.…”
Section: Effect Of Obesity On the Course Of Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in patients with CD disease using visceral adiposity as a measure of obesity have more consistently shown the increased risk of CD-related complications than those using BMI as a marker of overall obesity [58][59][60][61][62][63][64]. Erhayiem et al [58], in a study on 97 patients with CD, found that using computed tomography (CT) scanning that mesenteric fat index (MFI), defined as the ratio of areas of visceral-to-subcutaneous fat was a good marker of aggressive CD.…”
Section: Effect Of Obesity On the Course Of Ibdmentioning
confidence: 99%
“…These observations were confirmed in study by Li et al [59] also using CT scanning method; they found that visceral fat area and MFI values were associated with postoperative recurrence of Crohn's disease. Bryant et al [60], in a prospective study on 97 patients with CD, used dual energy X-ray absorptiometry (DXA) as a method to assess VAT. They also reported that VAT/subcutaneous adipose tissue [SAT] ratio, rather than BMI, was associated with structuring CD behaviour, an increase in disease activity, and reduced QoL.…”
Section: Effect Of Obesity On the Course Of Ibdmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) and obesity are increasing in incidence and prevalence worldwide ( 1 ). Increased adiposity has been shown to worsen the clinical outcomes of IBD including increased frequency of disease flares, postoperative recurrence, and stricturing/penetrating complications ( 2 6 ). The antitumor necrosis factor-alpha (TNFα) agents are effective in treating IBD but have a primary nonresponse rate of 10%–30% and secondary loss of response (SLOR) rate of 10%–15% per year ( 7 ), which may be attributed to several patient and disease- and treatment-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…31 Furthermore, a study in adults has shown an association between visceral adiposity and stricturing behaviour in patients with CD. 32 Obesity rates in children with IBD based on BMI assessment range between 8.4% and 16% in a number of studies. [9][10][11][12] In two of these studies, obesity is more prevalent in UC patients than CD patients.…”
Section: Discussionmentioning
confidence: 99%